Developing Junior High School Students English Reading Workbook Based on Local Culture in The Merdeka Curriculum (Development research in the seventh-grade students of SMPN 3 Air Besar in the Academic year 2023-2024): English - Nasri Kurniawan; Dwi Riyanti; Regina (Journal of English Development, 2024)
This study aimed to develop an English reading workbook based on local culture for students in SMPN 3 Air Besar following the Merdeka Curriculum. The research adopted the Research and Development (R&D) method using the ADDIE model, collecting data through questionnaires, interviews, and direct observations. Analyzed using descriptive statistics and content analysis, the results were used to revise the workbook and improve its effectiveness. The validation phase involved expert judgment from education, English language teaching, and local culture experts, indicating that "English Reading Workbook based on local culture" was culturally relevant, engaging, and effective in promoting English language learning. It serves as a valuable material for English language learning at SMPN 3 Air Besar, providing a culturally relevant and engaging way for students to learn English. The structured approach ensures the materials meet student needs and promote effective English language learning.